The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/pits.21903
|View full text |Cite
|
Sign up to set email alerts
|

What Good Is Gratitude in Youth and Schools? A Systematic Review and Meta‐analysis of Correlates and Intervention Outcomes

Abstract: The development of gratitude in youth has received increasing attention during the past several years, and gratitude-based interventions have often been recommended for use in schools. Yet, the empirical status of the correlates of gratitude and the effects of gratitude-based interventions on youths' outcomes remains unclear. The present study addressed this ambiguity by systematically reviewing and meta-analyzing original empirical journal articles investigating gratitude in youth through September 2014 (N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 46 publications
1
28
0
3
Order By: Relevance
“…By implication, policies and programs to enhance youth well-being could consider these interrelationships in developing interventions. However, as Renshaw and Olinger Steeves (2016) reported, more research regarding the effectiveness of gratitude interventions to promote well-being is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By implication, policies and programs to enhance youth well-being could consider these interrelationships in developing interventions. However, as Renshaw and Olinger Steeves (2016) reported, more research regarding the effectiveness of gratitude interventions to promote well-being is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, gratitude may motivate adolescents to engage in future benevolent actions (Froh, Bono, & Emmons, 2010). A recent meta-analysis (Renshaw & Olinger Steeves, 2016) suggested that gratitude is positively correlated to life satisfaction and negatively correlated to distress. Gratitude can be intentionally practiced, and some studies reported that engaging in gratitude activities lead to enhanced SWB in adolescents (Froh, Sefick, & Emmons, 2008; Khanna & Singh, 2016).…”
Section: Gratitudementioning
confidence: 99%
See 1 more Smart Citation
“…Previous research indicates that gratitude is associated with a wide range of positive psychological outcomes (see Renshaw & Steeves, 2016 for a review). Gratitude is linked to higher positive affect (McCullough et al, 2002) and life satisfaction (Datu, 2014; Datu & Mateo, 2015; Froh, Emmons, Card, Bono, & Wilson, 2011; McCullough et al, 2002; Wood, Joseph, & Maltby, 2008; 2009).…”
mentioning
confidence: 99%
“…Furthermore, as previous studies concentrated on exploring the association of gratitude with school adjustment and well-being outcomes, Renshaw and Steeves (2016) point out that “there is little evidence to suggest that gratitude in youth has practically meaningful associations with performance-based or informant-rated variables that educators and school psychologists tend to value” (p. 300). Although Froh et al (2011b) have assessed the relationship between gratitude and academic outcomes in the Western context, the study did not explicitly examine the factorial validity of the gratitude questionnaire.…”
mentioning
confidence: 99%